CULTURA POLÍTICA BRASILEIRA, PRÁTICAS PENTECOSTAIS E NEOPENTECOSTAIS: A presença da Assembléia de Deus e da Igreja Universal do Reino de Deus no Congresso Nacional (1999-2006) - Baptista, Saulo de Tarso Cerqueira (2007)
This thesis presents an analysis of the political practices of Pentecostal and Neopentecostal congressional representatives of the Assembly of God and the Universal Church of the Kingdom of God in the Congress of the Republic of Brazil, from 1999 to 2006. It compares the practices of Pentecostals and Neopentecostals with the standards of behavior of Brazilian political culture and actions related to the National State as preserver of culture. The religious agents of the referred to Churches are studied based on the investment of their Churches in national politics, in relation to Constitutional Amendments of 1987-1988, but the time frame of the research refers to two legislative periods, from 1999 to 2006. The main focus of the analysis is the Evangelical Parliamentary Front founded in 2003. The involvement of Pentecostals and Neopentecostals in cases of corruption and the appropriation of public resources, known as mensalão and mafia dos sanguessugas , is given special attention in the last chapter of the research.(AU)